Social Media Marketing Strategies for Electronic Cigarettes: Content Analysis of Chinese Weibo Accounts - Xinyi Zhou; Xinyu Hao; Yuhang Chen; Hui Deng; Ling Fang; Lingyun Zhang; Xiaotao Yan; Pinpin Zheng; Fan Wang (JMIR Publications, 2024)
BackgroundE-cigarettes have gained popularity among teenagers due to extensive marketing strategies on social media platforms. This widespread promotion is a risk factor, as it fosters more positive attitudes toward e-cigarette use among teenagers and increases the perception that using e-cigarettes is normal. Therefore, the marketing of e-cigarettes on social media is a serious global health concern, and its strategies and impact should be clearly identified. ObjectiveThis study examined how e-cigarette companies popularize their products via Weibo and identified the specific strategies influencing the effectiveness of their marketing. MethodsIn phase 1, we conducted a search on Qcc.com and identified 32 e-cigarette brands with active Weibo accounts between October 1 and December 31, 2020, along with 863 Weibo posts. The data were investigated through content analysis. The codebook was developed into four categories: (1) product and features, (2) sales and promotions, (3) social contact and interaction, and (4) restrictions and warnings. To further understand the factors influencing e-cigarette brand marketing, we conducted a multiple linear regression analysis. ResultsMarketing tactics by e-cigarette companies on Chinese social media were documented, including emphasizing attractive product features, using trendy characters, implicit promotions, downplaying health concerns, and engaging with Weibo users in various ways. Out of 863 posts, 449 (52%) mentioned product characteristics. In 313 (36.3%) posts, visible figures were used to attract attention. Product promotion was absent in 762 (88.3%) posts, and purchase channels were not mentioned in 790 (98.3%) posts. Social interaction-related posts received attention (n=548, 63.5%), particularly those featuring hashtag content (n=538, 62.3%). Most posts did not include claims for restrictions on teenagers' purchases or use (n=687, 79.6%) or information on health warnings (n=839, 97.2%). Multiple linear regression analysis identified marketing strategies that effectively increase the exposure of e-cigarette posts on Weibo. Posts including engagement via posts encouraging reposts, comments, and likes (P<.001) and engagement topics related to e-cigarette brands were positively correlated with the number of reposts (P=.009). Posts highlighting nonmonetary incentives (P=.004), posts with age restriction statements (P<.001), engaging via stories and idea collection (P<.001), and engagement topics related to products (P<.001) and current affairs (P=.002) had a positive effect on the number of comments. Engagement topics related to brands (P<.001) or interactive sweepstakes (P<.001) had a positive effect on the number of likes. ConclusionsE-cigarette posts on Weibo that focus on product features and social interaction attract public attention, especially from teenagers. Stricter regulations and monitoring should be adopted to restrict the social media marketing of e-cigarettes.